The Use of IT and its Impact on HRM Functions Performance and Organisation Performance. (Global Business Management Review (GBMR), 2012)
This paper aims to investigate the relationship between the use of information technology in organizations and its impact on the performance of human resource management in terms of their functions, and organizational performance in general. The performance of HRM functions as a mediating variable between the Use of IT and the organizational performance. The hypothesis is: When IT is used in organizations, the HRM functions will be converted to electronic HR and will affect positively the performance of HRM function which leads to increased organizational performance.